2009
DOI: 10.1017/s0031182009005678
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes to the tegumental system and the gastrodermal cells in adult Fasciola hepatica following in vivo treatment with the experimental fasciolicide, compound alpha

Abstract: Sheep infected with the triclabendazole-susceptible, Cullompton isolate of Fasciola hepatica were dosed with 15 mg/kg of compound alpha at 12 weeks post-infection. Adult flukes were recovered from the bile ducts at 24, 48 and 72 h post-treatment (p.t.). Ultrastructural changes to the flukes were assessed using transmission electron microscopy (TEM), with a view to gathering information on the mechanism(s) of action for compound alpha and on the possible route of its entry into F. hepatica. The tegumental syncy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…This is indicative of disruption to the osmoregulatory function of the tegument (Fairweather et al 1999). Similar observations have been made in previous studies involving TCBZ.SO (Stitt and Fairweather 1994;Halferty et al 2009a) and various other fasciolicides (Fairweather et al 1986;Skuce et al 1987;Skuce and Fairweather 1990;Anderson and Fairweather 1995;Meaney et al 2004Meaney et al , 2005Meaney et al , 2007McConville et al 2006McConville et al , 2007McConville et al , 2008McConville et al , 2009McKinstry et al 2007McKinstry et al , 2009Halferty et al 2009b). The severe swelling of the basal infolds would account for the general swelling of the tegument observed in the previous SEM study (Devine et al 2010c); if allowed to continue, this would lead to the sloughing of the tegument.…”
Section: Discussionsupporting
confidence: 89%
“…This is indicative of disruption to the osmoregulatory function of the tegument (Fairweather et al 1999). Similar observations have been made in previous studies involving TCBZ.SO (Stitt and Fairweather 1994;Halferty et al 2009a) and various other fasciolicides (Fairweather et al 1986;Skuce et al 1987;Skuce and Fairweather 1990;Anderson and Fairweather 1995;Meaney et al 2004Meaney et al , 2005Meaney et al , 2007McConville et al 2006McConville et al , 2007McConville et al , 2008McConville et al , 2009McKinstry et al 2007McKinstry et al , 2009Halferty et al 2009b). The severe swelling of the basal infolds would account for the general swelling of the tegument observed in the previous SEM study (Devine et al 2010c); if allowed to continue, this would lead to the sloughing of the tegument.…”
Section: Discussionsupporting
confidence: 89%
“…The apparent contradiction between drug peaks, drug half-life and drug action has been seen in other drug studies on F. hepatica (e.g. Meaney et al, 2003;McConville et al, 2008McConville et al, , 2009b. For these drugs, which are relatively slow-acting, it may take some time before their action (and the morphological changes they induce) to become apparent; however, the effects are seemingly irreversible, as the drug continues to act following its elimination from the host.…”
Section: Discussionmentioning
confidence: 96%
“…The spines (S) are partially obscured by the surrounding tegument. Bar 10 µm McConville et al (2009b), and they can help to explain the disruption visible externally. After 24 h treatment, there was a greater number of secretory bodies in the syncytium, due to accelerated transport from the tegumental cells, and this is part of a generalized stress response by the fluke, as observed in studies on other fasciolicides (Fairweather et al 1987;Skuce and Fairweather 1990;Buchanan et al 2003;McKinstry et al 2003;Meaney et al 2003Meaney et al , 2006Halferty et al 2008Halferty et al , 2009Toner et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The tegument also plays a number of important roles in fluke biology, including protection against immune attack and anthelmintic action (Hanna 1980;Fairweather et al 1999). The present results will be compared with those of a parallel SEM study on juvenile flukes from the same sheep trial ) and with the internal ultrastructural changes observed in adult flukes treated in vivo with compound alpha (McConville et al 2009b). …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation